Bone marrow-mesenchymal stem cells alleviate microglial Pyroptosis after intracerebral hemorrhage in rat by secreting C1q/tumor necrosis factor-related protein 3 - Wang, Qinghua; Piao, Jifeng; Li, Yulong; Tu, Huiru; Lv, Dingyi; Hu, Libin; Zhang, Run; Zhong, Zhenzhong (Experimental neurology, 2023)
There are no specific treatment methods for intracerebral hemorrhage (ICH). Neuroinflammation triggered by microglial pyroptosis plays an important role in ICH pathophysiology. Bone marrow mesenchymal stem cells (BMSCs) are widely used in the treatment of neurological diseases because of their paracrine function. In this study, we aimed to clarify whether BMSCs can alleviate microglial pyroptosis after ICH by secreting C1q/tumor necrosis factor-related protein 3 (CTRP3), a adiponectin paralog with established metabolic regulatory properties and neuroprotective effects. In an in vitro study, microglia were stimulated with hemin for pyroptosis and then co-cultured with BMSCs, CTRP3, or CTRP3-small interfering RNA (siRNA)-BMSC; in an in vivo study, intracerebroventricular transplantation of BMSCs or siRNA-CTRP3-BMSCs was performed after ICH surgery. The expression of inflammation-related factors was detected by qRT-PCR and ELISA. Western blotting and immunofluorescence staining were performed to detect the expression of pyroptotic protein, and western blotting was used to detect the activation of phosphoinositide 3-kinase (PI3K), protein kinase B (AKT) and splenic tyrosine kinase (Syk). Behavioral changes were detected 7 days after transplantation. ELISA and qRT-PCR results showed that the production of inflammatory cytokines in hemin-stimulated microglia was significantly downregulated following pretreatment with BMSCs or CTRP3. The Caspase-1 activity assay kit and western blotting results showed that BMSCs attenuated microglial pyroptosis by secreting CTRP3. Furthermore, the modulation functions of BMSCs or CTRP3 involve the promotion of PI3K/AKT and inhibition of Syk signaling pathway activation. Neurological deficits, edema, and disruption of tight junction protein were completely alleviated, while inflammation-related factors and microglial pyroptosis after ICH were significantly downregulated after BMSCs administration. BMSCs can inhibit neuroinflammation by inhibiting microglial pyroptosis, thus alleviate ICH symptoms, likely by suppressing the Syk signaling pathway while promoting the PI3K/AKT signaling pathway activation through producing CTRP3. •Pyroptotic Microglia Is Increased in the Injured Basal Ganglia Following ICH.•Administration of BMSCs moderated brain damage in rats with ICH through CTRP3.•BMSCs attenuated microglial pyroptotic cell death in rats after ICH through CTRP3.•BMSCs secreting CTRP3 attenuated microglial pyroptosis by regulating PI3K/AKT and Syk signaling pathway in rats after ICH.